Ensemble classification and its application to visual tracking - Zhang, Le (2016)
In machine learning and statistics, ensemble methods employ multiple models to obtain better performance than that could be obtained from any of the constituent (base) models [1]. Many studies have been published, both theoretical and empirical, which demonstrate the advantages of ensemble methods for classification.